2018
DOI: 10.1016/j.jcis.2017.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Gold core/ceria shell-based redox active nanozyme mimicking the biological multienzyme complex phenomenon

Abstract: Catalytically active individual gold (Au) and cerium oxide (CeO) nanoparticles (NPs) are well known to exhibit specific enzyme-like activities, such as natural catalase, oxidase, superoxide dismutase, and peroxidase enzymes. These activities have been maneuvered to design several biological applications such as immunoassays, glucose detection, radiation and free radical protection and tissue engineering. In biological systems, multienzyme complexes are involved in catalyzing important reactions of essential me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 52 publications
0
73
0
Order By: Relevance
“…CeO 2 is a well-established antioxidant agent in biomedicine [10,11]. The antioxidant properties of CeO 2 can be enhanced when it is combined with certain metals such as gold, silver or platinum [12][13][14][15][16], which have been proposed as biocompatible materials acting as radical scavengers and catalase-like enzymes to treat oxidative stress (OS) [14,[17][18][19][20]. Furthermore, it has been suggested that CeO 2 NPs, alone or in combination with metals, protect against radiation and have beneficial effects on different pathologies such as dementia and infection [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 is a well-established antioxidant agent in biomedicine [10,11]. The antioxidant properties of CeO 2 can be enhanced when it is combined with certain metals such as gold, silver or platinum [12][13][14][15][16], which have been proposed as biocompatible materials acting as radical scavengers and catalase-like enzymes to treat oxidative stress (OS) [14,[17][18][19][20]. Furthermore, it has been suggested that CeO 2 NPs, alone or in combination with metals, protect against radiation and have beneficial effects on different pathologies such as dementia and infection [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the nanozyme exhibited optimum SOD and catalase activity at neutral pH and for peroxidase, it was found at acidic pH. Finally, the nanozymatic (peroxidase mimetic) activity was utilized for the detection of glucose in a range from 100 µM to 1 mM in a time span of 5 min and at pH 4 (Bhagat et al 2017 ). Additionally, Wu et al developed a magnetic core–shell microgel system with immobilized GOx and HRP molecules.…”
Section: Bio-sensing Applications Of Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…Peroxidation activity is characteristic for Co 3 O 4 nanoparticles (Jia et al, 2016), Cu 2 O Guo et al, 2017), FeS (Dutta et al, 2012), CeO 2 (Sun et al, 2017), Au/CeO 2 (Bhagat et al, 2018), CoFe 2 O 4 (Fan & Huang, 2012), BiFeO 3 (Luo et al, 2010), MnFe 2 O 4 (Vernekar, et al, 2016), CdS (Garai-Ibabe et al, 2014), FeSe (Dutta et al, 2012), FeTe (Jiang et al, 2013), rhodium (Choleva et al, 2018), ZnFe 2 O 4 (Zhao et al, 2013), graphene oxide (Vineh et al, 2017), fullerene (Voeikov & Yablonskaya, 2015) and carbon nanotubes (Wang et al, 2014). This allows them to be applied for immunoassay, glucose detection, protection against free radicals, etc.…”
Section: Nanomaterials As Peroxidase Mimeticsmentioning
confidence: 99%